2023
DOI: 10.3390/molecules28030982
|View full text |Cite
|
Sign up to set email alerts
|

Antihyaluronidase and Antioxidant Potential of Atriplex sagittata Borkh. in Relation to Phenolic Compounds and Triterpene Saponins

Abstract: The genus Atriplex provides species that are used as food and natural remedies. In this work, the levels of soluble phenolic acids (free and conjugated) and flavonoids in extracts from roots, stems, leaves and flowers of the unexplored Atriplex sagittata Borkh were investigated by LC-ESI-MS/MS, together with their antioxidant and antihyaluronidase activity. Phenolic acids were present in all parts of A. sagittata; and were most abundant in the leaves (225.24 μg/g dw.), whereas the highest content of flavonoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…halimus L., Atriplex nummularia, Atriplex laciniata L., and A. sagittata Borkh. ,,,, In the present study, Atriplex sibirica L. is selected as a source of biologically active substances, and the possibility of using A. sibirica L. as a source of additional nutrients for the activation of reproduction of S.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…halimus L., Atriplex nummularia, Atriplex laciniata L., and A. sagittata Borkh. ,,,, In the present study, Atriplex sibirica L. is selected as a source of biologically active substances, and the possibility of using A. sibirica L. as a source of additional nutrients for the activation of reproduction of S.…”
Section: Introductionmentioning
confidence: 96%
“…The antihyaluronidase and antioxidant potential of Atriplex sagittata Borkh toward phenolic compounds and triterpene saponins has been highlighted. 31 with the chemical composition, antibacterial and antioxidant activity has also been established. 32 Safety of use and absence of toxicity to living organisms of the substances released from Atriplex L. have been proved in numerous studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As well as cardiovascular disease, it is also used in the treatment of anemia trouble and rheumatism. [10] Recent studies reported antioxidant, [15][16][17][18] Antiinflammatory, [19] Antimicrobial [20,21] , hypoglycemic, [22,23] Hepatoprotective, [24] anti-Alzheimer, [25,26] antidiabetic [9,27] and Wound healing [15] properties of plant extracts and phytochemicals from Mediterranean saltbush.…”
Section: Introductionmentioning
confidence: 99%